PERAN ORANG TUA DALAM MEMOTIVASI BELAJAR AL-QUR’AN PADA ANAK DI TPA SIDOMULYO KOTA PALANGKA RAYA - Satria Nur Rizki; Ajahari Ajahari; Surawan Surawan (SEKOLAH TINGGI AGAMA ISLAM AL-HUSAIN MAGELANG, 2022)
This study aims to describe the role of parents in motivating children to learn the Qur'an at TPA Sidomulyo and the supporting and inhibiting factors. The research method uses descriptive qualitative methods with data collection techniques using observation, interviews, and documentation. The subjects selected were parents who had children reading the Koran at the TPA using purposive sampling. In the results and discussion found several indicators will be described regarding the role of the parents. This research was conducted in Sidomulyo, Tumbang Tahai Village, Palangka Raya City. The results of this study found the role of parents in motivating their children to learn the Qur'an. The role of parents in motivating learning the Qur'an is influenced by several factors, namely supporting factors, 1) the will of the child, 2) the child's motivation, and 3) the environment, as well as inhibiting factors, 1) laziness, and 2) the busyness of parents.